2017
DOI: 10.18632/oncotarget.16376
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin resistance is determined by the regulation of topoisomerase I degradation mediated by ubiquitin proteasome pathway

Abstract: Proteasomal degradation of topoisomerase I (topoI) is one of the most remarkable cellular phenomena observed in response to camptothecin (CPT). Importantly, the rate of topoI degradation is linked to CPT resistance. Formation of the topoI-DNA-CPT cleavable complex inhibits DNA re-ligation resulting in DNA-double strand break (DSB). The degradation of topoI marks the first step in the ubiquitin proteasome pathway (UPP) dependent DNA damage response (DDR). Here, we show that the Ku70/Ku80 heterodimer binds with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…CPT-induced TOP1cc also induce DSBs, which activate DNA-PK that reduces the induction of RND1 . DNA-PK could reduce the induction of RND1 by promoting TOP1 proteolysis as previously reported 22 , 52 . Albeit in a lesser extent, ATM, which can activate DNA-PK 22 , also reduces the induction of RND1 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…CPT-induced TOP1cc also induce DSBs, which activate DNA-PK that reduces the induction of RND1 . DNA-PK could reduce the induction of RND1 by promoting TOP1 proteolysis as previously reported 22 , 52 . Albeit in a lesser extent, ATM, which can activate DNA-PK 22 , also reduces the induction of RND1 .…”
Section: Discussionsupporting
confidence: 74%
“…TOP1cc also activates a PARP-1-RND1 pathway that counteracts the induction of apoptosis [2]. DNA-PK-dependent DSB signaling prevents RND1 induction, possibly by promoting TOP1cc removal 22 , 52 [3]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that topo I is phosphorylated by DNA-PKcs at serine-10, and the resulting phosphoprotein (topoI-pS10) is efficiently ubiquitinated and targeted for rapid proteasomal degradation[3]. Protein phosphatases have been shown to interact with DNA-PKcs and could serve as upstream regulators of DNA-PKcs.…”
Section: Resultsmentioning
confidence: 99%
“…Our siRNA library screen of nuclear phosphatase identified PTEN and CTDSP1 as two phosphatases that significantly enhance the CPT induced topoI degradation. Importantly, we have demonstrated that PTEN regulates DNA-PKcs kinase activity in this pathway and PTEN deletion ensures DNA-PKcs dependent higher topoI-pS10, rapid topoI degradation and irinotecan resistance[3]. We asked if CTDSP1 also dephosphorylates DNA-PKcs, and is the upstream regulator of CPT induced topoI degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation